2009
DOI: 10.1016/j.agee.2009.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Development and critical evaluation of a generic 2-D agro-hydrological model (SMCR_N) for the responses of crop yield and nitrogen composition to nitrogen fertilizer

Abstract: C d), T s -base temperature at which f Nmin (t) equals 1 ( o C), T soil -daily mean soil temperature (ºC), U N -potential N uptake (kg ha -1 ), U Nr -potential N demand by fibrous roots (kg ha -1 ), W -dry weight of the entire plant excluding fibrous roots (t ha -1 ), W r -dry weight of fibrous roots (t ha -1 ), Z osmo -soil depth used in the calculation of mean osmotic pressure (cm), Z smin -depth of soil below which no N mineralization is assumed to take place (cm), ΔW r -root dry weight increment (t ha -1 ). Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…For example, Bechini et al (2006) carried out experiments in northern Italy from 1986 to 2001 to quantify the dynamics of aboveground biomass, plant N concentration, and N uptake and used the measurements for testing the CropSyst model. Other similar studies can be found in a large body of literature (Groot and Verberne, 1991;Li et al, 2009;Zhang et al, 2009;Biernath et al, 2011).…”
Section: Introductionsupporting
confidence: 72%
“…For example, Bechini et al (2006) carried out experiments in northern Italy from 1986 to 2001 to quantify the dynamics of aboveground biomass, plant N concentration, and N uptake and used the measurements for testing the CropSyst model. Other similar studies can be found in a large body of literature (Groot and Verberne, 1991;Li et al, 2009;Zhang et al, 2009;Biernath et al, 2011).…”
Section: Introductionsupporting
confidence: 72%
“…In this case, regarding the mineralization "large" set, sites with soil pH around neutral or slightly alkaline would have high (near one) membership values (Figure 5d). Nitrogen mineralization is a rather complex process concerning various inaccuracies stemming from soil characteristics and is usually quantified through deterministic models [21,22]. In the present study, the fuzzification scheme used allows a more structured way of dealing with such uncertainties through the partial inclusion (membership) in one or more linguistic sets.…”
Section: Resultsmentioning
confidence: 99%
“…with the soil and atmosphere. Recently, soil models linked to crop models have been developed to simulate the dynamics of element fluxes in soils (Keating et al 2003;Zhang et al 2009). While useful for agricultural management, these models focus on the photosynthesis of the main crop and on soil-plant relationships and ignore biological interactions between plants (including weeds) and between plants, animals, and microorganisms living in agroecosystems.…”
Section: From Plant-based Models To Agroecosystem Modelsmentioning
confidence: 99%